Analisis Pemutusan Kontrak Kerjasama Pengadaan Barang Atau Jasa Pemerintah Secara Sepihak - Imelda Kurniawati (Uniku Law Review, 2024)
Termination of Cooperation Contract for Procurement of Goods or Services" refers to the termination or cancellation of an agreement between parties involved in the procurement process of goods or services. The purpose of this article is to find out about the unilateral termination of the contract carried out by the Public Works and Spatial Planning Service of the Meranti Islands Regency against PT. Merbau Indah Abadi in the contract agreement in accordance with the regulations in force in Indonesia and also to analyze the basis for the judge's considerations that granted the plaintiff's lawsuit in the decision of the Pekanbaru State Administrative Court Number 21 / G / 2023 / PTUN.PBR. The research method used is the normative research method, the reason for using normative research in this study is because of the problems being studied. The results of this study are that in the decision, the Public Works and Spatial Planning Service of the Meranti Islands Regency was proven to have missed the unilateral termination mechanism explained in Presidential Regulation No. 4/2015 and Minister of Finance Regulation 243 / PMK.05 / 2015, so that the act of terminating the contract cannot be justified because it is not in accordance with the relevant laws and regulations. The conclusion is that there are legal consequences of unilateral termination of the contract in the procurement of goods/services contract, namely the imposition of administrative sanctions, sanctions in the form of inclusion in the blacklist, civil lawsuits and criminal reporting to the authorities.